2013
DOI: 10.1136/jech-2012-201883
|View full text |Cite
|
Sign up to set email alerts
|

Influence of room heating on ambulatory blood pressure in winter: a randomised controlled study

Abstract: Intensive room heating decreased morning BP and the morning BP surge in winter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…Association of Temp amb and daytime SBP was also consistent with the association of PET with ambulatory BP among 1897 hypertensive patients [17]. This result is concordant with our previous randomized controlled study among 146 healthy young participants that a 108C lower bedroom temperature (24.2 vs. 14.28C) did not induce significant difference in night-time SBP (105.7 vs. 105.9 mmHg) and increase sleep-trough MBPS and prewaking MBPS [27]. We found significant association of morning Temp in and Temp amb with sleep-trough MBPS and prewaking MBPS, and did not find significant association of night-time Temp in and Temp out with night-time SBP.…”
Section: Discussionsupporting
confidence: 90%
“…Association of Temp amb and daytime SBP was also consistent with the association of PET with ambulatory BP among 1897 hypertensive patients [17]. This result is concordant with our previous randomized controlled study among 146 healthy young participants that a 108C lower bedroom temperature (24.2 vs. 14.28C) did not induce significant difference in night-time SBP (105.7 vs. 105.9 mmHg) and increase sleep-trough MBPS and prewaking MBPS [27]. We found significant association of morning Temp in and Temp amb with sleep-trough MBPS and prewaking MBPS, and did not find significant association of night-time Temp in and Temp out with night-time SBP.…”
Section: Discussionsupporting
confidence: 90%
“…In spite of the convincing amount of evidence for the influence of cold ambient temperature on BP it is amazing that in most studies BP measurements were compared only with outdoor environmental air temperature data provided by meteorological institutes. This shortcoming can be easily improved by direct personal-level environmental temperature recording (PET) [4,17,18]. Because of the obvious relationship that PET affects the body's physiology via the skin, it is a logical step to include also ST (the "interface-variable" between body core and ambient temperature) measurements with respect to ambient temperature induced changes in BP.…”
Section: Introductionmentioning
confidence: 99%
“…The study from Ciccone et al (2011) shows that the number of overweight adults who live in the room with 20°C is larger than the number of the adults who lived in the room with 18°C of indoor temperature. Saeki et al (2013), studying on the influence of indoor heating on human ambulatory blood pressure in winter, found that the high indoor temperature index is in direct proportion to high blood pressure [12].…”
Section: Background and Literature Reviewsmentioning
confidence: 99%